Kajian Kualitas Air dan Penentuan Status Mutu Air Rawa Bendungan Cilacap - Hanief Wibowo Kurnianto; Endang Widyastuti; Ismangil Ismangil (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Rawa Bendungan is one of the water resources which is open for public. This condition has caused excessive utilization and ignorance of sustainability. Fishery waste, the tofu industry, cow farm, and agriculture around Rawa Bendungan have led to the decrease in water quality and endanger the sustainability of ecological functions and benefits of Rawa Bendungan. The aims of this study was to find out the condition of the physical, chemical, and biological parameters and to determine the quality status of Rawa Bendungan. Parameters of physical, chemical, and biological were analyzed descriptively. Determination of water quality status by STORET analysis. The average yield measurements of physico-chemical parameters include transparency (25.67-68 cm), TSS (34-66.67 mg/l), temperature (28-31 °C), pH (6-7), dissolved oxygen (2.47-7.47 mg/l), free CO2 (3.23-8 mg/l), BOD5 (1.53-14.53 mg/l), COD (24-85.33 mg/l), ammonia (0.0903-0.1803 mg/l), nitrite (0.0094-0.0997 mg/l), nitrate (0.8125-3.5072 mg/l), and orthophosphate (0.0265-0.1460 mg/l). Phytoplankton community consists of 48 species of Chlorophyta (191,808 ind/l; 47.26%), 29 species of Chrysophyta (105,948 ind/l; 25.98%), 8 species of Cyanophyta (64,152 ind/l; 15.73%), and 12 species of Euglenophta (44,712 ind/l; 10.96%). Rawa Bendungan waters are included in the category of heavily polluted by tofu industry and agriculture waste, moderately polluted by fishery waste, and lightly polluted by cow farm waste.